Comparison of aggression in married men and women - Riffat Sadiq (Journal of the Pakistan Medical Association, 2022)
Abstract Objective: To examine aggression in married men and women in comparison to each other. Method: The comparative cross-sectional study was conducted from January to September 2017 in Jinnah, Lyallpur, Madina and Jaranwala towns of Faisalabad in the Punjab province of Pakistan, and comprised an equal number of married men and women. Data was collected using a demographic information form and the Aggression Questionnaire. SPSS 20 was used for data analysis. Results: Of the 300 subjects, 150(50%) each were men and women. Among the men, 90(60%) and 110(73%) among the women were in the 31-40 years age bracket. The men showed significantly higher tendency towards physical aggression while verbal aggression was found more in women (p<0.05). The difference was non-significant with respect to anger and hostility (p>0.05).